1992
DOI: 10.1002/jmv.1890370102
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Lassa virus elicits a non protective immune response in rhesus monkeys

Abstract: We attempted to protect three rhesus monkeys from Lassa fever by vaccination with a preparation of purified whole Lassa virus which had been inactivated by gamma irradiation. The vaccinated monkeys developed antibodies against the three major viral proteins of Lassa virus demonstrated by radioimmunoprecipitation. When the three vaccinated monkeys and two unvaccinated control monkeys were challenged all five became severely ill and died. Prior to death a secondary, high-titer antibody response to Lassa virus wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 22 publications
0
41
0
3
Order By: Relevance
“…However, after challenge all the monkeys showed viremia and died. The inactivated Lassa virus vaccine based on gamma irradiation could not protect the animals after challenge [97].…”
Section: Gamma Irradiationmentioning
confidence: 98%
See 1 more Smart Citation
“…However, after challenge all the monkeys showed viremia and died. The inactivated Lassa virus vaccine based on gamma irradiation could not protect the animals after challenge [97].…”
Section: Gamma Irradiationmentioning
confidence: 98%
“…This inactivation procedure has been investigated for FMDV, Rauscher leukemia virus, HSV [96] and Lassa virus (Table 8) [97]. Inactivation kinetics showed that Rauscher leukemia virus and HSV were inactivated at a dose of 25 kGy.…”
Section: Gamma Irradiationmentioning
confidence: 99%
“…Development of vaccines against Lassa virus and Junin virus demonstrate the requirement for cellular immunity. Inactivated Lassa virus used in primates was able to induce antibodies against the nucteoprotein and glycoproteins, but not anti-Lassa cellular responses, and could not protect against Lassa infection [21]. Similarly inactivated XJ-clone 3 of Junin virus used as a vaccine in guinea pigs generated antibodies but was not protective [33], but priming guinea pigs or monkeys with live-attenuated Junin virus, produced protective immune responses [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…Lange et al (1985) subcutaneously injected 3000 PFU (Plaque Forming Unit) to Rhesus monkeys to find out the effect of virus in different organs of the monkeys. McCormick et al (1992) experimented with 10 4 PFU Lassa virus subcutaneously injected to inactivated viral vaccinated Rhesus monkeys. In experiments performed by Lukashevich et al (2005), inbred guinea pigs and rhesus monkeys were inoculated with cloned MOPV (Mopeia virus) and ML29 (mixture of RNA from MOPV and Lassa Virus ) then challenged with a Lassa virus of dose 10 3 PFU.…”
Section: Methodsmentioning
confidence: 99%